Analysis of green economy development strategy priorities in Madura using analytic network process approach - Royali, Ahmad Sayuti; Sholiha, Farra Ummush (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
The purpose of the study is to analyze the priorities of the Green Economy development strategy on Madura Island. Using the Analytic Network Process (ANP) Approach. Along with the rapid economic development supported by industrial developments and sophisticated technology brings many changes to nature which ultimately cause climate change or Climate Change this can occur due to an increase in temperature on the earth's surface. quantitative research approach with the Analytic Network Process-Super Decisions method, the primary data used is obtained directly sourced from expert respondents, academic experts, policy experts and practitioners as direct actors. The results show that the analysis of strategy priorities results in the main choice of strategies that encourage regulation of fossil fuel use, monitoring of environmental activities, green sector tax incentives, and the passage of nature convergence regulations.